Pengaruh Pengembangan SDM dan kompensasi Terhadap Kinerja Karyawan Melalui Motivasi Kerja Sebagai Variabel Intervening Pada UMKM di Kota Padang - Fadillah Fitri Mulya; Irenda Nindiya Pratiwi; Yollanda Septi (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of human resource development and compensation on employee performance through work motivation in MSMEs in the city of Padang. The research method used is a quantitative approach with survey techniques. Data was collected through questionnaires distributed to 100 MSME employees in the city of Padang. The research results show that human resource development has a positive and significant effect on employee work motivation. The better the development of human resources, the more employee work motivation will increase. Compensation has a positive and significant effect on employee work motivation. The better the compensation received, the more employee work motivation will increase. Work motivation has a positive and significant effect on employee performance. The higher the employee's work motivation, the greater the employee's performance will increase. Human resource development and compensation have a positive and significant effect on employee performance through work motivation. This means that human resource development and good compensation will improve employee performance by increasing work motivation.